A novel approach for obtaining bubble dissolution measurements at sea - Costa, R; Roy, R; Commander, K; Johnson, V; Colbert, A (International Commission for Acoustics, 1998)
A Hybrid system for measuring the dissolution of gas bubbles in an oceanic environment was developed utilizing the Coastal Systems Station’s Light Scattering Bubble Counter (LSBC). The LSBC independently measures flow velocity and bubble size, and is capable of distinguishing bubbles from particulate matter. In the hybrid system, the dynamic range of the LSBC measurements is 50 microns to about 300 microns in radius. The system is filled at depth in the sea purged of all gas, and then closed from the outside environment. A steady flow is established and clean air is forced through a ceramic fritted disk to create the initial bubble population. This bubbly mixture is re-circulated through the system at a nominal flow rate of 22 liters/min, which corresponds to a velocity of 30 cm/s through the LSBC aperture. The bubble radii are continuously measured using the LSBC, resulting in time-dependent bubble size distributions. These distributions are used to estimate bubble dissolution rates for the size range indicated.